Interactive web-based virtual reality with Java 3D - Ko, Chi Chung; Cheng, Chang Dong.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book provides both advanced and novice programmers with comprehensive, detailed coverage of all of the important issues in Java 3D"--Provided by publisher.
Appendix A. Downloading Software -- B. Running the Rotating Cube Program -- C. ViewManager -- D. Main Applet for Web-Based 3D Experiment -- E. Scene Graph Implementation for Web-Based 3D Experiment -- F. Knob Class for Web-Based 3D Experiment -- G. Navigation and Collision Detection for Web-Based 3D Experiment -- H. Picking for Web-Based 3D Experiment -- I. Program Summary and Screen Capture -- About the Authors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 26, 2010).
Keywords: Java3D.; Java (Computer program language); Computer graphics; Three-dimensional display systems; Virtual reality; Animation objects; Animation thread class for continuous movement; Aural environment; Canvas 3D configuration; Clip connecting for signal generator terminals; ConeSound; Customizing picking behavior class; Downloading software; Frame cycle time; Geometry objects; Interactive 3D Computer Graphics; Java3D program for a RotatingCube; Keyboard navigation; Knob class; Lighting, fog, and background; Main applet; Main mouse release event functions; Navigation detection; Picking for Web-based 3D experiment; PointSound; Ray segment picking shape; Scene graph implementation; Shape3D; Trigger point of oscilloscope; ViewManager; Virtual reality and JAVA 3D; VRML based circuit board object; Wakeup condition and criterion; Web-based virtual reality; Window eyepoint policy; Electronic books